Mampu Merancang dan Mengembangkan Desain Model Pembelajaran SD Berorientasi Dalam Peningkatan Mutu Kehidupan Berdasarkan Pancasila. - Yogie Pratama; Sefia Aisyah Tri Junaidi; Indri Puspita Sari; Citra Dewi Sangdia Pitaloka (SNHRP, 2023)
This study aims to understand the models of teaching and to find out what are the main models of teaching.Models of teaching in the sense that they are seen as more prominent and relevant to the demands of the needs of the world of education.Modification, especially of some teaching methods, the preparation is done entirely in the context of development or adjustment to needs.To prospective teachers and professional teachers are also expected to make necessary adjustments to the model if it is deemed necessary to match with the teaching-learning context which may be different from what is compiled in this section.Learning design is the practice of preparing communication technology media and content to help enable effective transfer of knowledge between teachers and learners. The design of learning is also a design of the learning process based on learning needs and objectives as well as the delivery system so that it becomes a reference in its implementation to create effective and efficient learning by minimizing students' difficulties in understanding learning.On the personal development of students by paying more attention to the life of the sense domain, especially the emotional side.